The Effect of Organizational Commitment and Quality of Work Life on Organizational Citizenship Behavior during Pandemic in Wastewater Management Company PD PAL Banjarmasin - Shilma Irvania; Meiske Claudia (Center for Journal Management and Publication, 2022)
The purpose of this research is to determine and analyze : (1) the influence of Organizational Commitment and Quality Of Work Life (QWL) on OCB, (2) the influence of Organizational Commitment on OCB, and (3) the influence of Quality Of Work Life (QWL) on Organizational Citizenship Behavior (OCB) in PD PAL Banjarmasin City. This research uses explanatory research. The respondents of this study were 31 employees of PD PAL Banjarmasin City. The sampling technique used is saturated sampling or census. Data collection techniques with questionnaires. This study uses 4 classical assumption tests, namely, multicollinearity, heteroscedasticity, normality and linearity tests. The data analysis technique uses Multiple Linear Regression Analysis with the help of SPSS 21 application software. The results of the F test showed that Organizational Commitment and Quality of Work Life (QWL) had a positive and significant effect on Organizational Citizenship Behavior (OCB). The results of the t-test of the Organizational Commitment variable have a positive and significant effect on Organizational Citizenship Behavior (OCB). While the t-test of the Quality of Work Life (QWL) variable has a positive but not significant effect on Organizational Citizenship Behavior (OCB).